Determination of edge-component Burgers vector of threading dislocations in GaN crystal by using Raman mapping. (9th October 2018) - Kokubo, Nobuhiko; Tsunooka, Yosuke; Fujie, Fumihiro; Ohara, Junji; Onda, Shoichi; Yamada, Hisashi; Shimizu, Mitsuaki; Harada, Shunta; Tagawa, Miho; Ujihara, Toru
Abstract: The threading edge dislocations in a GaN crystal are analyzed via micro-Raman spectroscopy mapping. A clear contrast image of the peak shift from a higher wavenumber to a lower wavenumber is simulated. The direction from the higher-wavenumber region to the lower-wavenumber region is found to be in the 90° rotation from the Burgers vector. The Burgers vector is experimentally determined to be using transmission electron microscopy. The magnitude of the Burgers vector agrees well between the simulated and experimental results. Thus, the density, direction, and magnitude of the edge component of the threading dislocations are identified using Raman spectroscopy mapping.